What do the inventories say about the urban trees of cities that were originally occupied by tropical forests? - Manfrim, Daniela Castelo Branco; Angélico, Talita dos Santos; Silva Filho, Demóstenes Ferreira da (National Journal of City Management, 2023)
Trees provide the urban population with many benefits as mental and physical well-being, property valorization, and climate change mitigation. To evaluate these benefits, it is necessary to know the species composition and distribution of trees in the urban landscape. For this purpose, the tree inventory is a fundamental instrument. This study aims to present an overview of scientific publications based on the street trees inventory of Brazilian municipalities. We expected to find information about the species composition and contributed to managers and decision-makers for species selection in new planting programs. We consulted four databases, initially identifying 322 articles published between 2000 and 2021. We considered 27 of them eligible for the systematic review. The studies are concentrated in cities in the Southeast and South regions. The authors of 21 articles reported quantifying or qualifying the street trees by focusing on planning. In general, species diversity was considered low, and the species mentioned as more abundant are Ficus benjamina, Moquilea tomentosa, and Cenostigma pluviosum. Exotic was predominant in 11 of 14 surveys that evaluated the origin of the species. These findings show that native flora is severely underrepresented on the streets in Brazilian cities. The alternative path for this scenario would be for the public managers to prioritize long-term actions and public policies starting from inventories that generate information about species composition and the potential environmental services provided by urban trees.